2007
DOI: 10.1093/ndt/gfl795
|View full text |Cite
|
Sign up to set email alerts
|

Post-allogeneic haematopoietic stem cell transplantation membranous nephropathy: clinical presentation, outcome and pathogenic aspects

Abstract: Our data suggest an association between cGVHD and post-HSCT MN. Treatment, mainly steroids and ciclosporin, should be aimed at the control of acute manifestations of cGVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
73
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 32 publications
3
73
0
Order By: Relevance
“…Although other reports have demonstrated treatment response with rituximab in hematopoietic cell transplantation patients with membranous glomerulonephritis/nephrotic syndrome, many previously reported patients had only partial remission, and in one case a biopsy was not performed. 4,6,22,29 Nevertheless, resolution of graft-versus-host disease and post hematopoietic cell transplant membranous glomerulonephritis with this anti-B-cell agent supports the hypothesis that B-cell alloreactivity may play a role in both of these entities. 16,35,37 Interestingly, our study also identified two patients with biopsy proven membranous glomerulonephritis after autologous hematopoietic cell transplantation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although other reports have demonstrated treatment response with rituximab in hematopoietic cell transplantation patients with membranous glomerulonephritis/nephrotic syndrome, many previously reported patients had only partial remission, and in one case a biopsy was not performed. 4,6,22,29 Nevertheless, resolution of graft-versus-host disease and post hematopoietic cell transplant membranous glomerulonephritis with this anti-B-cell agent supports the hypothesis that B-cell alloreactivity may play a role in both of these entities. 16,35,37 Interestingly, our study also identified two patients with biopsy proven membranous glomerulonephritis after autologous hematopoietic cell transplantation.…”
Section: Discussionmentioning
confidence: 66%
“…[4][5][6][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29] In our series, among seven patients with membranous glomerulonephritis, all five patients with allogeneic transplants had evidence of chronic graft-versushost disease, (in the non-membranous glomerulonephritis cohort, only three out of eight patients had chronic graft-versus-host disease). Importantly, we also present two patients with biopsy proven membranous glomerulonephritis after autologous hematopoietic cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…8,[10][11][12][13][14][15][16][17][18] These include membranous nephropathy, minimal change disease, and focal segmental glomerulosclerosis. In addition, acute and chronic thrombotic microangiopathy, or 'transplant-associated thrombotic microangiopathy,' has been shown to occur commonly in hematopoietic cell transplant recipients, 8,14,[17][18][19][20][21][22][23][24][25] with smaller reported numbers of membranoproliferative glomerulonephritis, proliferative glomerulonephritis, ANCA-associated glomerulonephritis, and IgA nephropathy. 8,18,[26][27][28][29][30][31][32][33][34][35][36][37] In studies also examining nonglomerular pathology, kidney specimens also show concomitant tubulointerstitial and vascular changes in hematopoietic cell transplant patients.…”
mentioning
confidence: 99%
“…8,18,[26][27][28][29][30][31][32][33][34][35][36][37] In studies also examining nonglomerular pathology, kidney specimens also show concomitant tubulointerstitial and vascular changes in hematopoietic cell transplant patients. 8,14,16,19,38,39 A few single-center studies of autopsy kidney specimen in the hematopoietic cell transplant population have been reported, including one large study focused primarily on thrombotic microangiopathy. 20,21,38,40 We retrospectively reviewed our single-center experience with renal pathology in specimens from three groups of hematopoietic cell transplant recipients.…”
mentioning
confidence: 99%
“…5 by immunodeficiency, hemorrhagic tendency, infections and engraftment syndrome (capillary leak syndrome), elevating the mortality rate to about 70%. 9 A little o 1% of survivors of AKI develop chronic GvHD-associated nephrotic syndrome within several years 10,11 and about 15-20% of them concomitantly develop CKD. 12 According to Lopes et al, 5 AKI after SCT is an important factor related to not only the mortality of patients but also the progression to CKD in the future.…”
mentioning
confidence: 99%